A dinâmica do Sistema Único De Saúde (SUS) na 8°Regional de Saúde do Paraná - Heimann, Moacir Roberto (2020)
This research analyzes the Unified Health System and its complementary practices (private networks agreed to provide health services), in the coverage area of the 8th Regional Health Region of Paraná, which applies SUS policies to 27 municipalities in the Southwest of Paraná. To achieve this goal, we started from the historical study of the formation of social policies in the health field. The historical outline took place from the 1930s, marked by changes in the economic and social dynamics of Brazil. It is during this period that social policies were institutionalized in order to create a health system capable of fulfilling the needs that the new situation presented. From this point on, we analyzed the evolution of health policies linked to the stages of development of Brazilian capitalism and its spatial dynamics until 2019. The theoretical basis is rooted in the concept of Social-Space Formation (SSF) proposed by Milton Santos in the 1970s, to analyze the reality from the entire relations of a given society. Thus, the research was organized as follows: in chapter I, we analyzed the emergence of public policies within the economic-political context of the Vargas Era. In the same period, we analyzed the policy known as “march to the west”, which influenced the formation of the Southwest of Paraná. Then, in chapter II, we presented the evolution of the region within the national context, as a means to highlight the particularities of the dynamics of the SSF per region and the dynamics of the formation of a Brazilian health system. The latter is a historical mark in the 1990s due to the implementation of SUS. At last, in chapter III, the analysis brought into discussion the dynamics and contradictions of SUS, from its formation (1988) to the present moment (2019).